2021
DOI: 10.3389/fchem.2021.727574
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Materials Incorporating Functional Porphyrins and Carbon Nanoplatforms as Building Blocks for Photovoltaic Energy Applications

Abstract: As a primary goal, this review highlights the role of supramolecular interactions in the assembly of new sustainable materials incorporating functional porphyrins and carbon nanoplatforms as building blocks for photovoltaics advancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 285 publications
(329 reference statements)
0
6
0
Order By: Relevance
“…They are also very attractive for a wide range of biomedical applications, such as cancer therapies (photodynamic and photothermal therapies (PDT and PTT), respectively) and early cancer diagnostics 30,31 as well as energy harvesting concepts ( e.g. dye-sensitized solar cells), 185 photodetectors 31 or sensors. 186–188 More detailed information regarding the use of porphyrin-functionalized graphene for these purposes is outside the scope of our review and can be found in the above-cited literature.…”
Section: Discussionmentioning
confidence: 99%
“…They are also very attractive for a wide range of biomedical applications, such as cancer therapies (photodynamic and photothermal therapies (PDT and PTT), respectively) and early cancer diagnostics 30,31 as well as energy harvesting concepts ( e.g. dye-sensitized solar cells), 185 photodetectors 31 or sensors. 186–188 More detailed information regarding the use of porphyrin-functionalized graphene for these purposes is outside the scope of our review and can be found in the above-cited literature.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al isolated three comprehend organic sensitizers from the C219 precursor and used only unique electron donors to increase the cell's V OC . 118 Wu et al projected the synthesis of two new organic dyes called the mas J5 and J6 that contain julolidine as the donor group (D) and cyano acidic corrosive or rhodanine-3-acidic corrosive as the electron acceptor (A) coupled via a bithiophene unit. The results confirmed that sensitizers are rapidly recovered and that the redox arbiter successfully captures the dye cations.…”
Section: Recent Improvements In Dsscsmentioning
confidence: 99%
“…Given the overwhelming performance of networked materials in many important areas that include energy, adsorption, storage, catalysis, and many more, they are also being utilized widely as electron transport materials in optoelectronic devices including solar cells and organic light-emitting diodes (OLEDs). [1][2][3][4][5][6] It seems that self-assembled networks help in improving the conducting capability of carrier transporting materials as many networked electron transport materials have been utilized to enhance the performance of devices. [7][8][9][10][11] Such solid-state self-assembled materials possess interconnected structures with a certain degree of porosity, which is beneficial for the conduction of the carriers.…”
Section: Introductionmentioning
confidence: 99%